2011
DOI: 10.3109/03630269.2011.630121
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Priming for Induction of Puberty in Thalassemia Patients with Pulsatile Reversible Hypogonadotrophic Hypogonadism

Abstract: Growth and pubertal disturbances are the most common causes of morbidity, affecting 60-80% β-thalassemia major (β-TM) patients worldwide, due mainly to hypogonadotrophic hypogonadism (HH). We undertook a 6-year prospective study of 55 Indian β-TM children with stunted growth and absent or arrested puberty, aged 15-18 years with pulsatile HH, to evaluate the role of low dose sex steroid priming (6-12 months) for physiological induction of puberty. Eighty percent responded favorably with increase in height, grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Chatterjee et al 2011 [39] have since confirmed feasibility for low dose sex steroid priming in their Indian cohort as 80% reached pubertal maturation which was most effective in younger patients with minimal iron overload.…”
mentioning
confidence: 99%
“…Chatterjee et al 2011 [39] have since confirmed feasibility for low dose sex steroid priming in their Indian cohort as 80% reached pubertal maturation which was most effective in younger patients with minimal iron overload.…”
mentioning
confidence: 99%
“…In CHH, a non‐response to LDSS is expected. In HC, pituitary siderosis is likely the main factor for DP and is often an irreversible condition, 43 although spontaneous recovery of the hypothalamus–pituitary–gonadal (HPG) function after a sex steroid priming has been also reported 66 …”
Section: Pathogenesis and Diagnostic Work‐upmentioning
confidence: 99%
“…The evidence that we have at the moment on females, however, is based mostly on β-Thalassemic patients, who are affected in 60-80% of the cases by hypogonadotropic hypogonadism: In a 6-year prospective study concerning children (boys and girls) with absent or arrested puberty and β-Thalassemia, sex hormones priming proved to be successful in inducing puberty in 80% of the subjects, suggesting that the estradiol priming could be as useful as the testosterone priming in the awakening of the hypothalamus-pituitary axis in the CDGP female patients 60 .…”
Section: Primingmentioning
confidence: 99%